2011
DOI: 10.1007/s00340-011-4801-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure and temperature fluctuations on near-infrared measurements of methane in underground coal mines

Abstract: This paper presents the findings of an investigation into the effects of pressure and temperature variations on methane concentrations measurements in near-infrared spectrum. A wavelength band was found where the spectral absorbance of methane is free from the interference of other common mine gases. The pressure and temperature variations that are expected in underground coal mines were found to have negligible effects on the uncertainty of spectroscopic measurement of methane concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Methane is a spherical-top tetrahedral molecule with four C-H bonds. The spectroscopic behaviour of methane has been studied extensively (Frankenberg et al, 2008;Shemshad et al, 2011) due to its importance in planetary and atmospheric processes, as well as in the mining industry.…”
Section: Spectroscopy Of Methane In the Near Infra-red Regionmentioning
confidence: 99%
“…Methane is a spherical-top tetrahedral molecule with four C-H bonds. The spectroscopic behaviour of methane has been studied extensively (Frankenberg et al, 2008;Shemshad et al, 2011) due to its importance in planetary and atmospheric processes, as well as in the mining industry.…”
Section: Spectroscopy Of Methane In the Near Infra-red Regionmentioning
confidence: 99%
“…Shemshad et al [12] investigated the most suitable band of methane absorption lines in near infrared spectrum. It was found that the Q band transitions of 2v 3 band make it a suitable target for spectroscopic detection of methane [12]. This can be experimentally and fundamentally discovered by investigating the detector output.…”
Section: Procedures Of 2f-wms Measurementsmentioning
confidence: 99%
“…Shemshad et el. [12] quantitatively studied the effects of pressure and temperature on the concentration measurement of methane applying 2f-WMS technique. Here, a new model is developed to quantify the effect of intensity variation on the methane concentration measurements as:…”
Section: Quantifying the Concentration Measurement Inaccuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen Sulphide (H2S) and Carbon Monoxide (CO) are the main mine gases that can be both toxic and explosive. Figure 2.1: Common hazardous mine gases [13][14][15][16] More than 50% of mine accidents including gas explosion, poisoning and suffocation are gasrelated [17]. According to the Mining Accident Database [18], gas explosion is the major source of accidents in Australian coal mines (Figure 2.2a).…”
Section: Mining Accidents Due To Gas Explosionmentioning
confidence: 99%